KAJIAN METAFORA PADA JULUKAN NEGATIF TERHADAP JOKO WIDODO DI MEDIA SOSIAL - Dede Fatinova; Eris Risnawati (Politeknik Negeri Jakarta, 2025)
Towards the end of his presidency in 2024, Joko Widodo came under intense scrutiny from the Indonesian public. Allegations of a political dynasty sparked widespread disappointment. This dissatisfaction was expressed through various metaphorically meaningful negative nicknames on the social media platform Instagram. The aim of this study is to analyze the metaphorical meanings embedded in the negative nicknames directed at Joko Widodo. The data consists of 25 negative nicknames found on Instagram, analyzed using the Conceptual Metaphor Theory proposed by Lakoff & Johnson (2003). The method employed is qualitative descriptive with a focus on content analysis. The results of the study shows that the metaphors used by Instagram users carry strong implications for Jokowi's political image. These nicknames associate him with authoritarianism, deception, nepotism, or the suppression of democracy. The use of such metaphors has the potential to damage Joko Widodo’s public image, especially when linked to public dissatisfaction with his administration’s policies.